Genomic diversity of drug-resistant Mycobacterium tuberculosis isolates in Lisbon Portugal: Towards tuberculosis genomic epidemiology. (March 2015) - Perdigão, João; Silva, Hugo; Machado, Diana; Macedo, Rita; Maltez, Fernando; Silva, Carla; Jordao, Luisa; Couto, Isabel; Mallard, Kim; Coll, Francesc; Hill-Cawthorne, Grant A.; McNerney, Ruth; et al.
Abstract: Multidrug- (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) present a challenge to disease control and elimination goals. Lisbon, Portugal, has a high TB incidence rate and unusual and successful XDR-TB strains that have been found in circulation for almost two decades. For the last 20 years, a continued circulation of two phylogenetic clades, Lisboa3 and Q1, which are highly associated with MDR and XDR, have been observed. In recent years, these strains have been well characterized regarding the molecular basis of drug resistance and have been inclusively subjected to whole genome sequencing (WGS). Researchers have been studying the genomic diversity of strains circulating in Lisbon and its genomic determinants through cutting-edge next generation sequencing. An enormous amount of whole genome sequence data are now available for the most prevalent and clinically relevant strains circulating in Lisbon. It is the persistence, prevalence and rapid evolution towards drug resistance that has prompted researchers to investigate the properties of these strains at the genomic level and in the future at a global transcriptomic level. Seventy Mycobacterium tuberculosis (MTB) isolates, mostly recovered in Lisbon, were genotyped by 24- loci Mycobacterial Interspersed Repetitive Unit – Variable Number of Tandem Repeats (MIRU-VNTR) and the genomes sequenced using a next generation sequencing platform – Illumina HiSeq 2000. The genotyping data revealed three major clusters associated with MDR-TB (Lisboa3-A, Lisboa3-B and Q1), two of which are associated with XDR-TB (Lisboa3-B and Q1), whilst the genomic data contributed to elucidating the phylogenetic positioning of circulating MDR-TB strains, showing a high predominance of a single SNP cluster group 5. Furthermore, a genome-wide phylogeny analysis from these strains, together with 19 publicly available genomes of MTB clinical isolates, revealed two major clades responsible for MDR/XDR-TB in the region: Lisboa3 and Q1. The data presented by this study contributes to the expanding knowledge of MTB genomic diversity yielding insights on microevolution and identification of novel compensatory mutations. Additionally, the analysis of non-synonymous/synonymous ratios revealed heterogeneities across the chromosome, genotype and Clusters of Orthologous Groups, highlighting possible and different evolution strategies. Overall, the results that are presented support the notion of an increasing genomic diversity that may support both setting and host adaptation.